Curcumin-derivative nanomicelles for the treatment of triple negative breast cancer. (16th May 2013) - Taurin, Sebastien; Nehoff, Hayley; Diong, Jasper; Larsen, Lesley; Rosengren, Rhonda J.; Greish, Khaled
Abstract: Background : Triple negative breast cancer (TNBC) is a subtype of breast cancer characterized by its poor outcome and a lack of targeted therapies. Recently, our laboratory has developed a second generation curcumin derivative, 3, 5-bis(3, 4, 5-trimethoxybenzylidene)-1-methylpiperidine-4-one (RL71) that shows potent in vitro cytotoxicity. RL71 is hydrophobic with poor bioavailability which limits its clinical development. Purpose : We have designed styrene-co-maleic acid (SMA) micelles encapsulating 5, 10 or 15% RL71 by weight/weight ratio to improve its solubility and pharmacokinetic profile. Methods : The micelles charge, size and release rate were characterized. We evaluated their cytotoxicity against TNBC cell lines. The internalization of the drug inside the cells was measured by HPLC and the efficiency of the micelles was tested using a tumor spheroid model. Results : The micelles exhibited mean diameters of 125–185 nm and had a neutral charge. SMA-RL71 micelles have a cytotoxicity profile comparable to the free drug against several TNBC cell lines. Moreover, the 15% loaded micelles increased the stability of RL71 and demonstrated higher activity in a tumor spheroid model. Conclusion: The current study demonstrates the efficiency of SMA for drug delivery, the influence of physicochemical characteristics on cytotoxicity, and provides the basis for preclinical testing in vivo .